2020
DOI: 10.1016/j.neunet.2019.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the stimuli encoding scheme of evolving Spiking Neural Networks for stream learning

Abstract: Stream data processing has gained progressive momentum with the arriving of new stream applications and big data scenarios. One of the most promising techniques in stream learning is the Spiking Neural Network, and some of them use an interesting population encoding scheme to transform the incoming stimuli into spikes. This study sheds lights on the key issue of this encoding scheme, the Gaussian receptive fields, and focuses on applying them as a pre-processing technique to any dataset in order to gain repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Otherwise, order nr is set to ord, ord is incremented and r is incremented. The computational complexity of Algorithm 1 is linear in the number of input neurons N I size , similarly to the encoding algorithms presented in [5] or [13].…”
Section: Ensure Precalculatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, order nr is set to ord, ord is incremented and r is incremented. The computational complexity of Algorithm 1 is linear in the number of input neurons N I size , similarly to the encoding algorithms presented in [5] or [13].…”
Section: Ensure Precalculatedmentioning
confidence: 99%
“…neurons of an eSNN are redistributed to encode the values of each bin of the histogram according to the cardinality of values in bins. As we present in the experiments, the offered encoding method provides much better classification accuracy than the other two encoding methods offered in the literature: a method that directly calculates the firing order of input neurons proposed in [5] and Gaussian Receptive Fields (GRFs) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Lobo et al (2020) have suggested the predictive potential of this encoding model and concentrated on how it was applicable as a computationally lightweight, model-agnostic pre-processing phase for learning the data stream. The main intuition of the circumstances under which the above-specified population encoding approaches produced efficient predictive gains in the classification of the data stream when pre-processing was not performed.…”
Section: Optimized Weight Updated Metalearningmentioning
confidence: 99%
“…It also suffers from the problem of measure of similarity. Evolving spiking NN (Lobo et al, 2020) modifies the closeness relationship among the data samples in the feature space that is being encoded and it also provides significant enhancements in the stream learner's predictive performance. Yet, from the detected drift, it cannot recover quickly and the encoded feature spaces cannot be adapted by the GRF.…”
Section: Ijwis 176mentioning
confidence: 99%
“…If the data from the grassroots can be effectively used, the valuable information hidden in the data can be mined, and the value of the data can be improved, which will provide decision-makers with a better factual basis and basis, thereby changing management methods and formulating better management and formulation to improve the quality and level of running schools [18,19]. Facing the massive data of higher education institutions, data mining technology is an intelligent information processing technology that can effectively discover knowledge from the massive data and can discover important information that people have previously ignored from the huge data information.…”
Section: Introductionmentioning
confidence: 99%